Stock Return, Currency and General Elections - Ong, Tze San; Soh, Wei Ni; Teh, Boon Heng; Ng, Sin Huei (Universiti Putra Malaysia Press, 2015)
The association between political elections and stock market performance for Malaysia market is discussed in this paper. This study aims to investigate the impact of General Elections in Malaysia on stock market indices. To provide additional support of the impact of general elections on stock returns through other channels, currency changes were also included in this study so as to discover the mediation effect of the exchange rate on the relationship between general elections and stock returns. Since the exchange rate does, to some extent, influence stock return, the relationship between exchange rates and stock returns during different stages of a general election cannot be overlooked. The results showed that currency change is negatively related with stock returns in pre-election and post-election stages, but it is not significant during the election period. The impact of currency on stock return exists as a mediation effect during election period. In a nutshell, the currency change directly impacts stock return with a negative influence. However, the direct relationship between currency and stock return disappears during the election week. Thus, stock return is affected by currency change indirectly